CONTRIBUTION OF BEDAH KAMPUNG AND RELOCATON PROGRAMTOWARD POVERTY ALLEVIATION –BEST PRACTISES OF SURAKARTA - Winny Astuti; Bonifacius Heru Santosa; Ana Hardiana (Journal of Architecture&ENVIRONMENT, 2015)
This research isconducted based on high poverty rates in Indonesia (17,4% in 2003) as well as in  Surakarta (14,1% in 2009). This is an urban phenomenon indicating the poverty, where in fact most of urban poors live in slums area, characterized by substandard houses with inadequate infrastructure and urban services. The approach of housing policy has shifted from provision approach  to sustainable development and recently to integration with poverty alleviation strategy. Community-based Housing Development is one of Housing Delivery Systems in Indonesia , which is based on Community Empowerment. This is believed to be the instrument for poverty alleviation as housing sector contributes in alleviation of poverty in terms of increasing access to housing and shelter ;  increasing access to services and infrastructure; social development and eradication of poverty; Environmental management; Economic development and governance. Objectiveof this research was to analyzethe contribution on CBHD-based programs toward poverty alleviation in Surakarta. Results of the research showed that higher contribution of poverty alleviation of CBHD Programs was access to housing due to higher intervention of the program in housing improvement. Relocation Program had higher contribution to poverty alleviation for the most components had been significantly increased:  condition of house construction, land secure tenure, water supply, sanitation condition, eventhough the program had displaced the people from previous location and increased transportation costs.